PRAKTIK MANAJEMEN RISIKO BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH (Studi Empiris pada Pegawai Bank Umum yang Menempati Posisi di Bidang Akuntansi Manajemen di Kota Semarang) - Muhammad Aritama Juniarto; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
This study aims to examine the factors that influence the risk management practices and differences of risk management practice between Conventional and Islamic Banks. There are several indicators that are used, level of understanding risk and risk management, risk identification, analysis and risk assessment, risk monitoring, risk management practice and credit risk assessment. This study was conducted by questionnaire survey of bank employees who occupy positions in the field of management accounting in the banks of Semarang city. The sampling method used in this study is simple random sampling, with a minimum sample size of 30 respondents. The statistical methods used to test the hypothesis is regression analysis and independent sample T-test. The results showed that the analysis and risk assessment and monitoring risks significant effect on risk management practice, while the level of understanding risk and risk management, risk identification and credit risk assessment is not significant effect on risk management practice. In addition the results of the study also showed no significant differences between Conventional and Islamic Banks in the level of understanding risk and risk management, risk identification, analysis and risk assessment, risk monitoring, risk management practice and credit risk assessment. Other findings obtained in this study is that reputation risk being the most important risk for conventional bank, while legal risks becoming the most important risk in Islamic Banks. In this study there are some limitations and shortcomings, namely, the difficulty of ensuring questionnaires which filled out by respondents according to respondents survey, so that the necessary repairs to the questionnaire used in this study by adding a control order respondents to fill out all the required data.